1960
DOI: 10.1042/bj0760610
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the ribitol teichoic acid from the walls of Bacillus subtilis

Abstract: 1. When [1:2 -14C2]ethanolamine, serine, L-[3H]serine or D-[3H]serine was administered orally to earthworms, serine ethanolamine phosphodiester and lombricine were found to be radioactively labelled.2. For each of the precursors the specific radioactivity of serine ethanolamine phosphodiester was greater than that of lombricine in both muscle and gut tissue.3. The specific radioactivity of serine ethanolamine phosphodiester and lombricine was greater in gut than in muscle. With [1:2-4C2]ethanolamine most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

1962
1962
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 19 publications
5
53
0
Order By: Relevance
“…Similar results with other organisms were reported by Armstrong, Baddiley & Buchanan (1960) and Hay et al (1965). Thus in lactobacilli the teichoic acid is made up of 7-6 units, in staphylococci of 8.1 and in B. subtilis of 8.9 units.…”
Section: Discussionsupporting
confidence: 78%
“…Similar results with other organisms were reported by Armstrong, Baddiley & Buchanan (1960) and Hay et al (1965). Thus in lactobacilli the teichoic acid is made up of 7-6 units, in staphylococci of 8.1 and in B. subtilis of 8.9 units.…”
Section: Discussionsupporting
confidence: 78%
“…The same observation on alkaline-resistant WTA has been reported in 1,3-linked poly(Gro-P) LTA of streptococci (Wicken & Baddiley, 1963). Under alkaline conditions, hydrolysis of the poly(Rbo-P) chain occurs through formation of cyclic phosphates in each ribitol residue, as described by Armstrong et al (1960). However, in the case of WTA from NRIC 1067 T , the glucose residues occupied hydroxyl groups at C-2 and C-4 of the ribitol residue, which are usually required to form the cyclic phosphate together with C-1 and C-5, respectively.…”
Section: Structural Analysis Of Gro-type Wtas From Snk50 Snk1 and Snk28supporting
confidence: 53%
“…Previous studies on the structures of TAs have so far indicated that WTA structures are more diverse than those of LTA, and that differences in composition and structure are observed not only at the species level but also at the strain level. Bacillus subtilis and Staphylococcus aureus strains are known to contain either Gro-P or Rbo-P repeating units in their WTA (Armstrong et al, 1960;de Boer et al, 1976;Baddiley et al, 1962;Endl et al, 1983), and in Listeria (Li.) monocytogenes, eight structures of WTA repeating units were discovered among strains with different serotypes, showing variation in the components of glycosyl residues and in the locations of phosphodiester bonds between repeating units (Uchikawa et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…While these molecules are clearly not oligo-or polysaccharides per se, their mode of synthesis is quite similar to those for many other bacterial glycoconjugates. It is (6,7,170). It remains to be determined whether these transporters, like some ABC transporters with NBDs found in groups C, D, and F, do not discriminate between the structures of the teichoic acid backbones.…”
Section: The Teichoic Acid Exporters-group E Nbdsmentioning
confidence: 99%